(untitled) (Research, Society and Development, 2020)
Agaricus subrufescens is a mushroom that produces laccase oxidoreductases that degrade dyes. Cultivation conditions such as nitrogen concentration, carbon source, and inducers can increase laccase production. This study aimed to cultivate A. subrufescens with urea, agro-industrial by-products, and inducers to produce laccase for dyes decolorization. Agaricus subrufescens U7-1 and U7-3 were grown in liquid medium with urea (0, 2, 4, 6, and 8 g L-1), carbon sources (glucose, sugarcane molasses - SuM and soybean molasses - SoM), and inducers (ethanol, guaiacol, vanillin, and veratryl alcohol). The enzymatic extract of the culture was used in the decolorization of remazol brilliant blue R (RBBR), reactive black 5 (RB5), and malachite green (MG). The laccase production of A. subrufescens was inversely proportional to the urea concentration and the greater U7-1 laccase activity occurred with 2 g L-1 urea and U7-3 produced more laccase without urea. SuM increased the laccase activity and anticipated the laccase peak of U7-1 in five days and U7-3 in 15 days. SoM reduced laccase activity. Vanillin increased the laccase activity of U7-1 by 29% (44380 U L-1) and anticipated activity peak; and vanillin and veratryl alcohol increased the laccase activity (44770 U L-1) of U7-3, but delayed activity peak. The extracts of U7-1 and U7-3 obtained from the vanillin culture discolored the RBBR in 24 h (65% and 75%), and VM (70%, 24 and 72 h), but did not reduce the color of PR5.